Business Succession in Indian Family Businesses in South Africa - Mahomed, Yaaser; Mtembu, Vuyokazi (Journal of Economics and Behavioral Studies, 2021)
Family businesses play a pivotal role economically and socially in most countries. The study aimed to identify and understand the experiences of Indian family businesses in South Africa with regard to business succession. A quantitative research approach was used with data collected through Google forms online survey. Data was collected from sixty (60) business people from Indian-owned family businesses in South Africa. The study interrogated the following factors which have an influence on family business succession: business ownership influence in succession, business readiness for the exit of owner and succession, the role of the owner after exit from business and selection criteria of the right successor. Findings revealed that the majority of families (86.27%) said it is important to have a hundred percent or full ownership of the business and that a successor should be selected within the family from their bloodline. Findings also revealed that the majority of businesses (86.27%) were not fully ready for the exit of the owner or current leader of the business and that on the exit of the owner; a majority (90.2%) of businesses will prefer to have the owner playing an active advisory role in the business. It is recommended that family-owned businesses should plan for succession on time and draft a well-planned strategic succession plan for the business. It is also recommended that an objective criterion be used in selecting a successor who will take the business forward. Healthy business continuity should be the ultimate goal of succession and families should not sacrifice successful business continuity because of their, internal differences and conflict, culture, blood relations, gender or religion.